Struts & frets - Skovron, Jon. (New York : Amulet Books, 2009)
Sammy wants to be a musician, as was his grandfather, but while the band he is in is self-destructing, Sammy is too distracted by his grandfather's decline and confused feelings about his best friend to fix it--and his mother stays too busy to help.
Keywords: Bands (Music) -- Fiction; Self-confidence -- Fiction; Interpersonal relations -- Fiction; Grandfathers -- Fiction; Single-parent families -- Fiction; Columbus (Ohio) -- Fiction